Degradation of BiTeCl induced by thermal and laser treatment - Wojciech Ryś; Iaroslav Lutsyk; Karol Szałowski; Maxime Le Ster; Maciej Rogala; Michał Piskorski; Paweł Krukowski; Paweł Dąbrowski; Rafał Dunal; Aleksandra Nadolska; Przemysław Przybysz; Klaudia Toczek; et al. (Scientific Reports)
Abstract This study examines the thermal stability and structural behavior of bismuth chloride telluride BiTeCl, a layered thermoelectric material with significant potential for energy conversion applications. Our investigations reveal that the chlorine-terminated surface exhibits poorer quality and increased defectivity compared to the tellurium-terminated side. The crystals were subjected to thermal annealing up to 520 K and green laser irradiation. Through techniques such as low-energy electron diffraction (LEED) and X-ray photoelectron spectroscopy (XPS), we found that while annealing enhances the crystallinity of the chlorine side up to 470 K, it ultimately suffers from thermal degradation above this temperature. The event leads to transformation into bismuth telluride - Bi2Te3 characterized by a lower BE shift of the Bi and Te bands by ~ 0.35 eV. The identity of the product was later confirmed via Raman spectroscopy while irradiating it with little laser power. With an increase in the power to 3.1 mW, it was however observed that the samples become locally modified undergoing similar degradation as during the annealing. The research demonstrates and characterizes the phenomena occurring during the decomposition either via irradiation or annealing. The explanation of such phenomena is then proposed based on the results of our theoretical DFT calculations. Additionally, we assess the usefulness of BiTeCl as a thermoelectric material, compare it in regard to the literature, and suggest new potential applications that may benefit from the transformation into Bi2Te3.